The Possible Protective Role of Selenium Supplementation Against Some Hormone Alterations Induced by Diclofenac Sodium in Female Rats - Nura Al-Zail; Marfoua Ali; Reem Abdalhalem; Ajab Abdalsttar (AlQalam Journal of Medical and Applied Sciences, 2025)
Diclofenac sodium (DFS) has affected the tests for serum hormones. Crucially, prior studies indicate that diclofenac functions as a thyroid protein antagonist. An important minor mineral that guards and prevents oxidative harm is selenium (Se). Aims: The goal of this study is to explore the negative impact of DFS, Se, and their combination on: some levels of serum hormones such as" thyroid stimulating hormone (TSH)", "triiodothyronine (T3)"," thyroxin hormone (T4"(, "follicle-stimulating hormone (FSH)", "luteinizing hormone (LH)” in female albino rats. Methods: Twenty albino female rats 170-200 grams, were randomly distributed into 4 groups of 5 rats. Untreated (1 ml distilled water for 21 days), Se cohort (0.25 mg per kg for three weeks), DFS cohort (10 mg per kg for 2 weeks), and protective cohort (Se + DFS). The protective group received Se for seven days, followed by Se and DFS two hours apart over two weeks. Results: The mean values revealed a notable decline in levels of T3, FSH, and LH, as well as a rise in the amount of TSH, PRL, and progesterone in the DFS group. Meanwhile, rats in the Se group revealed no notable variations in levels of TSH, T3, and FSH, but an increase in levels of T4, PRL, progesterone, and a decrease in LH and estrogen. The administration of Se with DFS was able to reduce and alleviate the harmful effects of DFS on most of the measured parameters. In conclusion, the findings of this research showed that Se effectively reduced thyroid hormone disorders and changes in female sex hormones in female albino rats.